Ondansetron use in nausea and vomiting during pregnancy: A descriptive analysis of prescription patterns and patient characteristics in UK general practice. Issue 10 (17th May 2022) - Slattery, Jim; Quinten, Chantal; Candore, Gianmario; Pinheiro, Luis; Flynn, Robert; Kurz, Xavier; Nordeng, Hedvig
Abstract : Aims: The objective of this study was to describe ondansetron drug utilization patterns during pregnancy to treat nausea and vomiting in pregnancy (NVP). Moreover, we aimed to describe the maternal factors associated with NVP and antiemetic use. Methods: The data consist of pregnancies with a live birth(s) within an IMRD‐UK registered GP practice. Descriptive statistics were used to investigate patterns of ondansetron use in pregnancy and to describe maternal characteristics associated with NVP and antiemetic drug utilization. We differentiate first‐ from second‐line use during pregnancy using antiemetic prescription pathways. Results: The dataset included 733 633 recorded complete pregnancies from 2005 to 2019. NVP diagnosis and ondansetron prescription prevalence increased from 2.7% and 0.1% in 2005 to 4.8% and 2.5% in 2019 respectively. Over the period 2015–2019, the most common oral daily dosages were 4 mg/d (8.5%), 8 mg/d (37.1%), 12 mg/d (37.5%) and between 16 and 24 mg/d (16.9%). Prescription of ondansetron was initiated during the first trimester of pregnancy in 40% of the cases and was moderately used as a first‐line therapy (2.8%), but preferred choice of second‐line therapy. Women with mental health disorders, asthma and/or prescribed folic acid were more likely to experience NVP and use antiemetics in pregnancy than their counterparts. Conclusion: This study confirms that ondansetron is increasingly used off‐label to treat NVP during pregnancy, also in the first trimester and before other prescription antiemetics have been prescribed. Several maternal comorbidities and folic acid use were more common among women experiencing NVP and using antiemetics, including ondansetron.